Biological functions of natural antisense transcripts - Werner, Andreas (BioMed Central, 2013)
In theory, the human genome is large enough to keep its roughly 20,000 genes well separated. In practice, genes are clustered; even more puzzling, in many cases both DNA strands of a protein coding gene are transcribed. The resulting natural antisense transcripts can be a blessing and curse, as many appreciate, or simply transcriptional trash, as others believe. Widespread evolutionary conservation, as recently demonstrated, is a good indicator for potential biological functions of natural antisense transcripts. See research article: http://www.biomedcentral.com/1471-2164/14/243